2021
DOI: 10.1007/s10570-021-04025-z
|View full text |Cite
|
Sign up to set email alerts
|

A simple method of simultaneously endowing paper or fluff pulp with both high softness or appropriate fluffing properties and antimicrobial properties

Abstract: As the living standard improve, disposable sanitary and living paper requires not only softness or easy to uff in a dry state, but also good antibacterial property. In this study, a series of alkyl quaternary ammonium salts (AQAS), a kinds of antibacterial-debonding agents, were synthesized by using a twostep process. The SN2 nucleophilic substitution reaction was designed between triethanolamine and sulfoxide chloride, and followed subsequent quaternization by tertiaryamines with different long alkyl chains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Inhibition zone experiments indicated that the obtained materials exhibit antibacterial properties against S. aureus and E. coli. Therefore, the authors suggest that these materials could have potential applications in antibacterial tissues or daily disposable sanitary products to prevent microbial contamination [124]. Xu and coworkers proposed compounds that were applied as antibacterial softening agents for paper processing.…”
Section: Gemini Surfactants and Polycationic Qacsmentioning
confidence: 99%
“…Inhibition zone experiments indicated that the obtained materials exhibit antibacterial properties against S. aureus and E. coli. Therefore, the authors suggest that these materials could have potential applications in antibacterial tissues or daily disposable sanitary products to prevent microbial contamination [124]. Xu and coworkers proposed compounds that were applied as antibacterial softening agents for paper processing.…”
Section: Gemini Surfactants and Polycationic Qacsmentioning
confidence: 99%
“…Debonding agents (DAs) are reagents which are typically applied to weaken the bonding force of bers and are usually used in the preparation of uff pulp, they can be categorized as cationic and nonionic (Xu et al 2021). Among them, cationic debonding agents (c-DAs) are composed of cationic groups (=N + =, -S + -, =P + , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…and hydrophobic groups. Xu et al (Xu et al 2021) synthesized a series of alkyl quaternary ammonium salts (AQAS) antibacterial-bonding agents by a two-step method. The obtained products can endow antibacterial properties and high softness to paper and control the appropriate burst strength, making it suitable for improving the properties of uff pulp.…”
Section: Introductionmentioning
confidence: 99%